THE EFFECT OF ILOPROST (ZK-36374) ON ISOLATED AND TRANSPLANTED PANCREATIC-ISLET CELLS - YEGEN, ŞEVKET CUMHUR (ELSEVIER SCI LTD, 1994)
Several methods have been described for the prolongation of survival of isolated and transplanted islet cells. To investigate the effect of a stable prostacyclin analogue, ZK 36374 (Iloprost) on isolated and allotransplanted islet cell function, we studied 6 groups of rats: Group 1 (n = 7) animals underwent pancreatectomy and their islets were isolated and cultured by standard techniques. Group 2 (n = 8) animals were treated the same, except for the addition of Iloprost to the culture solutions. Group 3 (n = 7) animals were treated as group 1, but the isolated islets were transplanted to the subcapsular space of the left kidney of group 5 (n = 7) animals. Group 4 (n = 8) animals were treated as group 2, and the isolated islets were transplanted to group 6 (n = 8) animals. The insulin levels in the culture media obtained in group 1 and 2 were measured. In groups 5 and 6 blood glucose levels were measured and intraperitoneal glucose loading tests were performed. Histological examination was performed for both isolated and transplanted islets. The results showed that both insulin levels and histologic evaluation were better for group 2 than group 1. Animals in group 6 reached normoglycemia on the fifth day following transplantation while it was the ninth day for group 5. The intraperitoneal glucose loading test was tolerated better by group 6 animals. We conclude that Iloprost may be responsible for the improved results which seem to be due to its cytoprotective effect.
Keywords: UK 38485; RATS; SITE; PROSTACYCLIN; ISCHEMIA; ANALOG; MOUSE